Skipjack Tuna Fishing Ground Based on Oceanography Satellite Image Data in Fisheries Management Area (FMA) 713 - Safruddin, Safruddin; Hidayat, Rachmat; Zainuddin, Mukti (Hasanuddin University, 2020)
This study aimed to map the oceanographic conditions and, based on that, to determine the favorable condition of skipjack tuna fishing ground in Fisheries Management Area (FMA) 713. This condition includes sea surface temperature (SST) and chlorophyll-a concentration. The primary data, such as fishing ground position and fish catch per trip, was collected by following the fishing operations that utilized pole and line (in Bone Gulf and Flores Sea) and purse seine fishing operations (in Makassar Strait). The secondary data, such as SST and chlorophyll-a, was derived from oceanographic satellite image data. The result showed that from January to August 2019, the skipjack tuna tends to occupy off shore areas where the sea surface temperature is between 29 - 29.5 oC and the chlorophyll-a density is between 0.10 to 0.15 mg.m3.